Studi Cross-Textual Reading Terhadap Kisah Padi Pulut dan Kisah Elia dan Janda di Sarfat - Jefri Andri Saputra; Mordekai Mordekai (Sekolah Tinggi Theologia Abdiel, 2023)
This study aims to provide an alternative regarding the attitude that the church should have in dealing with crises. The crisis referred to here refers to an economic recession. Following up on this effort, the author examines the story